2008
DOI: 10.1542/peds.2007-3758
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Genes and Cerebral Palsy: A Population-Based Study

Abstract: Two of the 28 single-nucleotide polymorphisms examined were associated with all types of spastic cerebral palsy in both gestational age groups and others with cerebral palsy in gestational age or cerebral palsy subgroups. Some of these associations support previous findings. There may be a genetic contribution to cerebral palsy risk, and additional investigation is warranted of genes and gene-environment interactions in cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 40 publications
2
41
1
Order By: Relevance
“…Recently, it was suggested that erythropoietin improved the outcome after ischaemia (23). A genetic contribution to the risk of CP has been detected by Gibson et al in a population-based study (24), whereas infectious or thrombophilic factors, for example, are highlighted by others (25,26). The origins of CP remain only partially explained, although the description and dating of the lesions are increasingly detailed, mainly due to the advances in neuroimaging (27)(28)(29)(30).…”
Section: Post-neonatal Casesmentioning
confidence: 99%
“…Recently, it was suggested that erythropoietin improved the outcome after ischaemia (23). A genetic contribution to the risk of CP has been detected by Gibson et al in a population-based study (24), whereas infectious or thrombophilic factors, for example, are highlighted by others (25,26). The origins of CP remain only partially explained, although the description and dating of the lesions are increasingly detailed, mainly due to the advances in neuroimaging (27)(28)(29)(30).…”
Section: Post-neonatal Casesmentioning
confidence: 99%
“…The genetic influences affecting CP have been the subject of much attention in recent years. [10][11][12]20,21 Several genes have been identified as risk factors, and have been categorized as thrombophilic, cytokine, apolipoprotein E and a group related to cardiovascular physiology and the functioning of the immune system. 21 Among the candidate genes, several SNPs of the MTHFR genes have been investigated either in normal populations or CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 A mounting body of recent evidence points to genetic influences on the occurrence of CP. This evidence includes familial data, 7 twin studies 8 and specific genetic factors, [9][10][11][12] and indicate that CP may be related to genomic factors, as well as to environmental incursions during brain development.…”
Section: Introductionmentioning
confidence: 97%
“…Children with CP have a decrease of adaptation resources, first of all, owing to affection of regulatory structures of CNS -hypothalamus, hippocampus and cerebral cortex [17,18].…”
Section: Introductionmentioning
confidence: 99%